Efficacy and safety of 5-aminolevulinic acid photodynamic therapy in refractory genital lichen sclerosus - Weiwei Shi; Fang Wang; Liangliang Chen; Ruzhi Zhang (Photodiagnosis and Photodynamic Therapy)
Background: Genital lichen sclerosus (GLS) is a chronic inflammatory skin disease affecting the genital and anal areas. Treatment of refractory remains a challenge in clinical practice. Objective: This study aimed to evaluate the efficacy and safety of 5-aminolevulinic acid photodynamic therapy (5-ALA PDT) for refractory GLS. Methods: Thirty-five patients with histopathologically confirmed GLS (including 32 females and 3 males) were treated with 5-ALA PDT. Lesion pretreatment was performed to enhance photosensitizer penetration, and fluorescence diagnosis was used for precise point-to-point treatment. Efficacy and safety were systematically evaluated by assessing treatment outcomes, symptom improvement, side effects and maintenance of efficacy over a 6-month follow-up period. Results: After treatment, most patients experienced significant relief of pruritus, improved skin elasticity and color, and reduced lesion area. After 6 treatment sessions, 11 patients (31.43 %) achieved complete resolution of pruritus, with 3 patients (8.57 %) achieving complete remission after 3 sessions. Cattaneo scores decreased significantly after treatment and during follow-up (P < 0.05). Adverse reactions were mainly mild pain, which could be relieved by ice compression or oral analgesics. Conclusions: 5-ALA PDT shows significant efficacy and good safety for refractory GLS, improving the clinical symptoms and signs of patients, and warrants wider clinical application.